Effect of experimental and seasonal warming on litter decomposition in a temperate stream - Ferreira, Verónica (2014)
Litter decomposition, a fundamental ecosystem process in woodland streams, is potentially affected by the predicted increase in water temperature. Here, we assessed the effects of experimental and seasonal warming on oak litter decomposition and on the relative contributions of microbes and invertebrates to this process. Experimental warming (*3 C) stimulated litter decomposition in the coldest, but not in the warmest, months. This may be attributed to (1) higher temperature sensitivity of decomposition at lower ambient temperature due to temperature limitation of enzymatic activity, (2) higher relative temperature increase in winter than in warmer months, (3) existence of a previous warming period in winter, and (4) stronger stimulation of the activity of detritivores by warming in winter due to the prevalence of earlier (smaller) instars than in warmer months. The low response of litter decomposition to warming may have been due to the low nutrient availability in the study stream. The 30-day litter decomposition was stimulated over the seasonal gradient (monthly mean temperature: 6–16 C), which may be attributed to a stimulation of metabolic activities by warming and to changes in detritivore life history over the seasons. The stimulation of litter decomposition with temperature suggests that the rate of CO2 release from freshwaters will increase under global warming. However, invertebrate-driven litter decomposition was more responsive to warming than microbial-driven litter decomposition, suggesting that a larger fraction of litter carbon may be converted into secondary production and stored in the system for longer periods.